Therapeutic Potential of Vasoactive Intestinal Peptide and its Receptors in Neurological Disorders - M. White, Caitlin; Ji, Sunggoan; Cai, Huan; Maudsley, Stuart; Martin, Bronwen (CNS & Neurological Disorders - Drug Targets, 2010)
Vasoactive intestinal peptide (VIP) is a basic 28 amino acid peptide that binds to a member of the class II family of G proteincoupled receptors (GPCRs). It is widely expressed throughout the body and plays an important role in numerous biological functions. VIP acts via three different GPCRs: VPAC1, VPAC2, and PAC1, which have been identified in various tissues, including brain, lung, kidney, gastrointestinal tract, tongue, and also on immunocompetent cells such as macrophages and lymphocytes. There is mounting evidence that VIP expression and signaling is altered in numerous neurological disorders, and it is becoming apparent that VIP and its receptors could be therapeutic loci for the treatment of several pathological conditions of the central nervous system. In this review, we describe the pathology of several major neurological disorders and discuss the potential pharmacotherapeutic role of VIP and its receptors for the treatment of disorders such as Alzheimer's disease, Parkinson's disease, and Autism Spectrum Disorders.
Keywords: vasoactive intestinal peptide